Optimization of esterase production from Monascus purpureus Y146 by artificial neural network-genetic algorithm and its application in flavor enhancement of fermented wine - Xue Yang; Sixu Lin; Yuning Zhang; Meiqi Lin; Chang Feng; Xuerui Yan (Food Microbiology, 2027)

Quantitative attribution of seasonal runoff variations in the Yellow River Basin under unsteady conditions using a modified Budyko framework - Junjie Wang; Yuning Chi; Shaoxiong Zhang; Bing Shi; Liting Zhang; Chenjun Du; Xin Li; Baoqi Li; Liqin Yang; Lei Huang; Dian Yuan; Kaiyang Qiu; et al. (Journal of Hydrology, 2026)

Formation mechanisms of a severe springtime ozone episode in the Beibu Gulf, China: The role of the marine “ozone pool” and regional transport - Runxi Pan; Fei Jiang; Shuzhuang Feng; Dewei Yang; Yuning Xie; Hang Li; Yu He; Mengwei Jia; Yanhong Xie; Bei Chen (Atmospheric Pollution Research, 2026)

Mangrove-inspired salt-excreting evaporator for enhanced solar desalination and mineral salt harvesting - Dengkai Xu; Jin Yang; Lixuan Zhao; Xiayuan Zhang; Yuning Liu; Xiaohua Jia; Haojie Song (Desalination, 2026)

An immunosensor integrating SERS and upconversion luminescence for dual-mode detection of CA125 in ovarian carcinoma - Shiyuan Wang; Jiaqi Yang; Junyu Chen; Yasheng Dai; Changgan Lai; Tao Jiang; Yuning Pan (Chemical Engineering Journal, 2026)

Coaxial electrospun TiO2@CuO heterojunctions with interfacial charge rearrangement for photothermal oxidation of toluene - Weimin Huang; Ke-Xin Li; Shuzhuo Bai; Shanshan Chen; Fanbin Meng; Bing Qin; Yuning Yang; Zonghui Liu; Wen-Tao Zheng; Zhun Hu (Journal of Environmental Chemical Engineering, 2026)

Multi-omics insights into Tenebrio molitor biodegradation of environmental wastes: Growth, transcriptional and metabolic adaptations - Tian Zhu; Wenzong Zhou; Weiwei Huang; Quan Yuan; Hang Yang; Yuning Zhang; Haotian Gu; Yongda Yuan; Weiwei Lv; Qichen Jiang (Biocatalysis and Agricultural Biotechnology, 2026)

Multiple macroeconomic benefits from mixed coastal flooding adaptation in China's coastal cities - Jiaju Lin; Shuyu Yang; Shuo Wang; Yuning Zhao; Yanhong Lin; Xiongzhi Xue; Yurong Ouyang (Ocean & Coastal Management, 2026)

Efficacy of traditional Chinese Medicine and antibiotics for bovine mastitis: A meta-analysis - Yang Ni; Huanqi Liu; Cailin Xu; Zhenbang Ye; Xueshu Han; Yuning Liu; Zhenjun Sun; Yongping Chen (Preventive Veterinary Medicine, 2026)

Improving the yield of Monacolin K in solid-state fermentation of Monascus purpureus H164 based on fermentation optimization strategy - Sixu Lin; Xue Yang; Qinghua Yu; Junyao Wang; Bing Li; Yuning Zhang; Xuerui Yan (Fungal Biology, 2026)

Outstanding extrinsic reversible self-healing material for commercial epoxy coating: Dynamic chemistry-based supramolecular interpenetrating polymer networks - Panhua Li; Tingting Luo; Xuanyu Lv; Yuning Shi; Bosen Zhang; Kaixuan Ma; Wanchun Guo; Kesong Tian; Xueai Li; Hui Ying Yang; Haiyan Wang (Chemical Engineering Journal, 2026)

Quercetin glycoside-incorporated lipid nanoparticles for mRNA delivery exhibit reduced inflammatory response - Yujing Shen; Yuning Wei; Weizhao Weng; Chunxia Yang; Chuanjun Wu; Xuyuan Liu; Xishan Xu; Jianping Qi; Wei Zhang; Ning Ding (Chemical Engineering Journal, 2026)

Highly homogeneous dispersed Ni/Co nanoparticles in carbon controlled by ion coordination to trigger polarization for enhanced microwave absorption - Yuning Shi; Shuang Zhang; Xueai Li; Chunsheng Wang; Hang Li; Jinjin Yang; Kexin Jin; Wanchun Guo; Kesong Tian; Yahui Wang; Haiyan Wang (Chemical Engineering Journal, 2026)

Biomimetic sequential immuno-osteogenic regulation via a dual-drug delivery system with PDA coating on sulfonated PEEK promotes bone defect repair - Zixuan Wu; Kai Ma; Xiaoyu Guo; Zidong Wu; Zheyue Zhu; Yuning Qu; Weidong Zhu; Chengxin Li; Rui Ma; Pei Yang (Chemical Engineering Journal, 2026)

Metals/Metalloids Profile in Seminal Plasma/Serum of Patients with Asthenozoospermia/Oligozoospermia: Correlation with Semen Quality - Yang Wang; Shiyuan Zhao; Yuning Liu; Junbo Zhang; Longqiao Cao; Pei Jiang; Yanyan Qiao (Biological Trace Element Research, 2026)

Behavioral responses of rice field eel (Monopterus albus) under ammonia nitrogen, pH, and nitrite stress based on machine vision - Yifan Zhao; Fei Zhou; Muyan Li; Wenzong Zhou; Weiwei Lv; Weiwei Huang; Hang Yang; Yuning Zhang; Mingyou Li; Zhen Xu; Quan Yuan (Aquaculture, 2026)

Identification of the geographical origin of wild rice field eel (Monopterus albus) in China by stable isotopes - Weiwei Lv; Muyan Li; Yangyang Lu; Yifan Zhao; Weiwei Huang; Hang Yang; Quan Yuan; Yuning Zhang; Mingyou Li; Wei Hu; Chunxia Yao; Danhe Wang; et al. (Food Control, 2026)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

γ-Aminobutyric acid and fat alter soymilk gel properties and functionality via protein remodeling - Kangyong Zhang; Hongwei Tang; Yuning Yang; Zhongjiang Wang; Bailiang Li; Fei Liu (Food Chemistry, 2025)

Improvement of methane production from waste activated sludge by ultrasound-activated peracetic acid oxidation - Hui Wang; Xuecheng Li; Yuning Yang; Yufen Wang; Tingting Zhu; Peizhe Sun; Bing-Jie Ni; Yiwen Liu (Chemical Engineering Journal, 2025)

Dual-functional 3D-printed polyetheretherketone scaffolds with immunomodulatory nano‑calcium silicate/interleukin-4 coating synergistically enhance osteogenesis through macrophage M2 polarization and NF-κB pathway suppression - Xiaoyu Guo; Yanwen Su; Zixuan Wu; Zidong Wu; Kaili Liu; Junyu Yue; Yuning Qu; Kunzheng Wang; Jiankang He; Rui Ma; Pei Yang (Chemical Engineering Journal, 2025)

Tire wear particle leachate induces lipid metabolism disorders in Procambarus clarkii, leading to liver inflammation and mitochondrial dysfunction in hepatocytes - Xianghan Liu; Qichen Jiang; Wenzong Zhou; Muyan Li; Chenxi Zhu; Quan Yuan; Yuning Zhang; Hang Yang; Weiwei Huang; Weiwei Lv (Marine Pollution Bulletin, 2025)

Efficient degradation of norfloxacin by CoWO4/CS/BiOCl-10 Z-type heterojunction photocatalysts based on hydrogen bonding and interfacial interaction - Xinyan Wang; Yuting Zhang; Jian Zhang; Chengpeng Shao; Jiaxing Yang; Yuning Zhang; Ruoyi Li; Zheng Xing (Journal of Environmental Chemical Engineering, 2025)

An injectable triple-responsive chitosan-based hydrogel encapsulating QCT-Cu self-assembled nanoparticles accelerating diabetic wound healing via remodeling the local microenvironment - Yan Zhu; Shiyuan Yang; Jia Zhou; Zixiao Zhang; Yue Hu; Qingyu Xu; Yuning Zhou; Yuanjin Xu (Carbohydrate Polymers, 2025)

Environmental Impacts and Behaviors of Chromium in Pakchoi-Soil Systems Under Ambient and Elevated CO2 Levels - Yuning Wang; Yatu Huang; Ye Ding; Wentao Yang; Yabo Wang; Qiao Xu; Yao Yao; Xiaozhi Wang; Meiling Xu (Water, Air, & Soil Pollution, 2025)

Identification and utilization of a novel large-effect QTL and linked markers for enhancing protein concentration in peanut - Mingjun Wang; Jianbin Guo; Gaorui Jin; Taihua Yang; Weigang Chen; Yuning Chen; Li Huang; Huaiyong Luo; Xiaojing Zhou; Boshou Liao; Huifang Jiang; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Aerodynamic load extraction in the real-time hybrid model test for floating wind turbine - Zhihao Jiang; Yuning Gao; Xinliang Tian; Gang Chen; Binrong Wen; Zhike Peng; Wei Zhang; Mindong Yang; Yang Gao (Ocean Engineering, 2025)

Preparation of polyvinyl alcohol/pullulan nanofibers and Eudragit® S100/polyvinyl alcohol/pullulan core-shell nanofibers for enhanced probiotic storage and oral viability - Yangrui Wang; Yingxue Yue; Shengjun Yang; Sufang Duan; Yuning Yang; Zhaozhi Wang; Xuetong Li; Bailiang Li; Yupeng Wang (Food Hydrocolloids, 2025)

Feline gastrointestinal eosinophilic sclerosing fibroplasia in a young ragdoll cat: with surgical management - Jindong Gao; Yuning Li; Yang Xie; Md. F. Rahim; Md. F. Kulyar; Quan Mo; Jianzhong He; Mengdi Zhang; Xing Wu; Jinhua Yin (Veterinary Research Communications, 2025)

Ginsenoside Rb2 Inhibits the Pyroptosis in Myocardial Ischemia Progression Through Regulating the SIRT1 Mediated Deacetylation of ASC - Yuning Li; Wenhua Zhang; Yamin Cai; Dong Yang (Biochemical Genetics, 2025)

Single-cell RNA sequencing reveals the heterogeneity of hepatopancreas cells and their association with gonadal development in the red swamp crayfish Procambarus clarkii - Lin Du; Yuning Hu; Siyu Lu; Xuguang Li; Jiajia Li; Hai Lin; Jiaxin Yang; Yu Xu; Zhiqiang Xu (Aquaculture, 2025)

The influence of γ-aminobutyric acid production and fat content on the gel properties, protein conformation, and nutritional characteristics of fermented milk: Achieved through interactions with milk proteins - Kangyong Zhang; Yang Cheng; Yuning Yang; Yuxing Li; Bailiang Li; Fei Liu (Food Chemistry, 2025)

Dissolved organic matter mitigates the toxicity of silver nanoparticles to freshwater algae: Effects on oxidative stress and membrane function - Jilai Zhang; Chenglei Hu; Ming Jiang; Qianqian Xiang; Sheng Wang; Youbo Su; Naiming Zhang; Zhihao Si; Yuning Mu; Ran Yang (Environmental Pollution, 2025)

Long-term rice-eel co-culture system effectively alleviated the accumulation of antibiotic resistance genes in soil - Qingqing Zhao; Wenzong Zhou; Weiwei Lv; Quan Yuan; Yuning Zhang; Hang Yang; Weiwei Huang; Weiguang Lv (Journal of Environmental Management, 2025)

Treatability of odorous dioxanes/dioxolanes in source water: How does molecular flexibility and pre-oxidation affect odorant adsorption - Qi Wang; Yuning Du; Wentao Li; Chunmiao Wang; Junzhi Zhang; Min Yang; Jianwei Yu (Water Research, 2024)

Transforming waste polystyrene foam to carbon on zeolite for efficient solar water desalination - Mingxin Yang; Hao Zhang; Yuning Fu; Zixuan Wang; Ying Zhang; Zhongwang Ding; Mingbo Yue (Journal of Environmental Chemical Engineering, 2024)

Synergistic photocatalytic-photothermal contribution induced by Pd-TiO2/PEDOT immobilized in PVDF membrane for enhanced water purification - Yacong Yang; Zhihao Cao; Tianhan Shen; Junyang Zhang; Zuofei Gu; Mingwan Zhao; Zongli Xie; Yingchun Miao; Yuning Huo; Hexing Li (Chemical Engineering Journal, 2024)

Regulation of tumorigenesis and ferroptosis in non-small cell lung cancer by a novel BBOX1-AS1/miR-326/PROM2 axis - Jinlu An; Jiang Shi; Chao Yang; Junfang Luo; Yuning Li; Jie Ren; Yuanjun Lv; Yang Zhang (Molecular and Cellular Biochemistry, 2024)

Protein Disulfide Isomerase Endoplasmic Reticulum Protein 57 (ERp57) is Protective Against ALS-Associated Mutant TDP-43 in Neuronal Cells - Sonam Parakh; Emma R. Perri; Marta Vidal; Zeinab Takalloo; Cyril J. Jagaraj; Prachi Mehta; Shu Yang; Colleen J. Thomas; Ian P. Blair; Yuning Hong; Julie D. Atkin (NeuroMolecular Medicine, 2024)
Amyotrophic Lateral Sclerosis (ALS) is a severe neurodegenerative disease affecting motor neurons. Pathological forms of Tar-DNA binding protein-43 (TDP-43), involving its mislocalisation to the cytoplasm and the formation of misfolded inclusions, are present in almost all ALS cases (97%), and ~ 50% cases of the related condition, frontotemporal dementia (FTD), highlighting its importance in neurodegeneration. Previous studies have shown that endoplasmic reticulum protein 57 (ERp57), a member of the protein disulphide isomerase (PDI) family of redox chaperones, is protective against ALS-linked mutant superoxide dismutase (SOD1) in neuronal cells and transgenic SOD1 G93A mouse models. However, it remains unclear whether ERp57 is protective against pathological TDP-43 in ALS. Here, we demonstrate that ERp57 is protective against key features of TDP-43 pathology in neuronal cells. ERp57 inhibited the mislocalisation of TDP-43 M337V from the nucleus to the cytoplasm. In addition, ERp57 inhibited the number of inclusions formed by ALS-associated variant TDP-43 M337V and reduced the size of these inclusions. ERp57 was also protective against ER stress and induction of apoptosis. Furthermore, ERp57 modulated the steady-state expression levels of TDP-43. This study therefore demonstrates a novel mechanism of action of ERp57 in ALS. It also implies that ERp57 may have potential as a novel therapeutic target to prevent the TDP-43 pathology associated with neurodegeneration.

Novel cow dung-doped sludge biochar as an efficient ozone catalyst: Synergy between graphitic structure and defects induces free radical pathways - Yuxuan Yang; Kedong Ma; Yubo Cui; Ke Zhao; Yuning Lu; Wanjun Zhang; Peijing Kuang; Xuejun Zou (Environmental Research, 2024)

Enhancing the electrochemical activation kinetics of V2O3 for high-performance aqueous zinc-ion battery cathode materials - Yuexin Liu; Chenlong Gao; Yuning Sun; Xuxia Hao; Zhengjie Pi; Menghao Yang; Xiaoli Zhao; Kefeng Cai (Chemical Engineering Journal, 2024)

Chemically renewable SERS sensor for the inspection of H2O2 residue in food stuff - Xin Tian; Yun Qin; Yuning Jiang; Xiaoyu Guo; Ying Wen; Haifeng Yang (Food Chemistry, 2024)

Fast and efficient in-situ construction of low crystalline PEDOT-intercalated V2O5 nanosheets for high-performance zinc-ion battery - Yuexin Liu; Tongde Wang; Yuning Sun; Mingcheng Zhang; Guohua Gao; Jinhu Yang; Kefeng Cai (Chemical Engineering Journal, 2024)

Development and experimental validation of a machine learning-based disulfidptosis-related ferroptosis score for hepatocellular carcinoma - Cong Zhang; Tiantian Xu; Kun Ji; Shoujin Cao; Jing Ai; Junhan Pan; Yunbo Cao; Yuning Yang; Li Jing; Jun-Hui Sun (Apoptosis, 2024)

Highly efficient base editing in rabbit by using near-PAMless engineered CRISPR/Cas9 variants - Zhongtian Zhang; Xinyu Wu; Jie Yang; Xin Liu; Ruonan Liu; Yuning Song (Science China Life Sciences, 2023)

Magnetically-oriented porous hydrogel advances wearable electrochemical solidoid sensing heavy metallic ions - Wanxin Tang; Zhen Gu; Yao Chu; Jian Lv; Li Fan; Xinling liu; Feng Wang; Ye Ying; Jian Zhang; Yuning Jiang; Jiaying Cao; Anni Zhu; et al. (Chemical Engineering Journal, 2023)

Stitching electron localized heptazine units with “carbon patches” to regulate exciton dissociation behavior of carbon nitride for photocatalytic elimination of petroleum hydrocarbons - Qi Guo; Yuning Wu; Linhong Xia; Xue-Fang Yu; Kaisheng Zhang; Yujie Du; Lixue Zhang; Hua Tang; Jianbo Cheng; Jianpeng Shang; Yanhua Peng; Zhuo Li; et al. (Chemical Engineering Journal, 2023)

Effects of azadirachtin on detoxification-related gene expression in the fat bodies of the fall armyworm, Spodoptera frugiperda - Haikuo Yu; Xianmei Yang; Jinghua Dai; Yuning Li; Sethuraman Veeran; Jintian Lin; Benshui Shu (Environmental Science and Pollution Research, 2022)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Tubular Localization and Tissue Distribution of Peptide Transporters in Rat Kidney - David E. Smith; Anna Pavlova; Urs V. Berger; Matthias A. Hediger; Tianxin Yang; Yuning G. Huang; Jürgen B. Schnermann (Pharmaceutical Research, 1998)